Teacher's Language Code Switching in Indonesian Language Learning in Class II, Elementary School 11 Sub-district Ulu Musi District Four Laws - Gustin Tri Arisa; Vebbi Andra; Hengki Satrisno (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
Code switching is a switch from one language to another or from one dialect to another or vice versa, the occurrence of code switching due to changes in certain situations. The use of language is very important because language is the most important thing so that humans can interact with each other, especially in the interaction of a more formal scope of learning. Learning is an effort to prepare teaching and learning activities by teachers for students. Teachers are people who are assigned to be responsible for the growth and development of students towards educated humans. In learning, teachers are emphasized to be able to apply Indonesian properly and correctly as a unified language, namely Indonesian, which is inversely proportional to the situation in the observed school. This study aims to determine the form of teacher language code switching and factors that influence teacher language code switching in Indonesian language learning in class II SD Negeri 11 Ulu Musi District, Empat Lawang Regency. The methods used are observation, interview, and documentation. It can be concluded that the code switching process carried out by Indonesian teachers in teaching and learning activities uses the type of internal code switching, namely the code switching of the teacher's language from Indonesian to local language, both learning activities in the introduction, core and closing phases. Factors that influence the teacher's language code switching, namely internal and external. Internally, teachers are not too confident to always use Indonesian. Then externally code switching occurs due to environmental factors that are accustomed to using local languages, so that speech partners find it difficult to understand messages conveyed with other than local languages.